Нові архівні матеріали до "одеських періодів" біографії міністра закордонних справ Української держави Г.О. Афанасьєва (1848-1925 рр.) - Березін, С. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
На матеріалах з фондів Державного архіву Одеської області, Національної бібліотеки України імені В.І. Вернадського (м. Київ) і Російської державної бібліотеки (м. Москва) документально підтверджуються маловідомі факти біографії Георгія Омеляновича Афанасьєва. Джерельна база дозволяє уточнити та доповнити наведені в історіографії свідоцтва про життя й творчість видатного представника вітчизняної інтелігенції за часів його перебування в Одесі, зокрема — про діяльність у
Новоросійському університеті. The article is based on archival materials from the collections of the State
Archives of Odessa Region, Vernadsky National Library of Ukraine (Kiev) and
the Russian State Library (Moscow). These materials provide documental
confirmation of the little-known facts of the biography of George Afanas`ev,
the famous historian and educator, journalist, banker and diplomat, public and
state figure. The represented source base allows to refine and supplement the
information from the historiography about the life and work of Afanas`ev in the
period of his stay in Odessa and activity in the Novorossiysky University. Some
of these documents are published and introduced into scientific circulation for
the first time.